Educação popular: instrumento de fortalecimento da sociedade civil - Trein, Eunice S. (1987)
The objective is to evidence the importance of the school as place to practice the popular education which be realized as a strengthening instrument of the civil society. As the knowledge transmitted by the school can be true and so efficient, the school, as an instrument of the dominant class, has the chance to be a way to the appropriation of knowledge for the dominated classes, which carry them to the conscious of their proper domination. The education is understood here as a part of a whole of society and entirely integrated by it. The society is by itself a dynamic entireness whose development process is a continuous dialectic process overtaking-conservation of each one of its phases. The study has started from analyzing the various political economic conjuncture of Brazil, since the thirties, and the several pedagogic proposals which corresponded to each period, aiming to explain their self-interaction. It ends by returning to the conjectural analysis of the eighties and identifying the challenge that is faced to the education today, that is: how the popular education, while strengthening instrument of the civil society, can contribute to the construction process of a democratic order within the Brazilian society.